2020
DOI: 10.1186/s13018-020-01840-1
|View full text |Cite
|
Sign up to set email alerts
|

A possible injectable tissue engineered nucleus pulposus constructed with platelet-rich plasma and ADSCs in vitro

Abstract: Background: Injectable tissue engineered nucleus pulposus is a new idea for minimally invasive repair of degenerative intervertebral disc. The platelet-rich plasma (PRP) and adipose-derived stromal cells (ADSCs) could be harvested from autologous tissue easily. PRP contains numerous autologous growth factors and has reticulate fibrous structure which may have the potential to make ADSCs differentiate into nucleus pulposus-like cells. The goal of this study was to explore the feasibility of constructing a possi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The disc signal in the ADSC combined with PRP group showed higher intensity than that in the other groups (Figure 6A) and was statistically significant in reversing disc degeneration (Figure 6B) (111). Similar therapies based on the combination of PRP and stem cells have been reported in many studies (113)(114)(115)(116), and the biological efficacy of PRP has been confirmed in the experimental results. With the addition of PRP, many types of stem cells can differentiate into NP cell phenotype, and the diseased intervertebral disc can be reversed and regenerated to a certain extent, which provides a potential feasible scheme for future clinical treatment.…”
Section: Promotion Of Degenerative Disc Regenerationsupporting
confidence: 74%
“…The disc signal in the ADSC combined with PRP group showed higher intensity than that in the other groups (Figure 6A) and was statistically significant in reversing disc degeneration (Figure 6B) (111). Similar therapies based on the combination of PRP and stem cells have been reported in many studies (113)(114)(115)(116), and the biological efficacy of PRP has been confirmed in the experimental results. With the addition of PRP, many types of stem cells can differentiate into NP cell phenotype, and the diseased intervertebral disc can be reversed and regenerated to a certain extent, which provides a potential feasible scheme for future clinical treatment.…”
Section: Promotion Of Degenerative Disc Regenerationsupporting
confidence: 74%
“…Hydrogels, which are composed of polymer networks capable of absorbing and retaining large amounts of water, have been recognized for their potential to serve as biological scaffolds 108 . For instance, some scholars have demonstrated the use of PRP hydrogel scaffolds in conjunction with AD-MSCs to construct injectable tissue-engineered nucleus pulposus in vitro 109 . This innovative approach has shown promise in minimally invasive repair of degenerative intervertebral disks.…”
Section: The Latest Applications Of Biomaterials: Optimizing Regenera...mentioning
confidence: 99%